Lecturers' Perceptions of The Use Of E-Evaluation In Assessing The Academic Achievement of Students Of The Islamic Religious Education Study Program - Ningsih, Wirda (Sekolah Tinggi Agam Islam Sumatera Medan, 2024)
Although E-evaluation technology offers the potential for increased efficiency and accuracy in assessment, there are still problems related to its understanding and application among lecturers. This study aims to analyze lecturers' perceptions of the use of electronic evaluation methods in assessing students' academic achievements in the Islamic education study program at STAI Al-Kifayah Riau. This research uses a mixed method. Data collection techniques using questionnaires and interviews. In this study, quantitative and qualitative data were converged. The research findings revealed that users' perceptions of E-evaluation in the Islamic Education study program of STAI Al-Kifayah Riau showed a high level of approval. The survey showed that respondents had a positive view of the use of E-evaluation. Meanwhile, the implementation of E-evaluation in the Islamic Education study program has a moderate level. Lecturers already have expertise and understanding related to E-evaluation after attending training, but they still face difficulties in implementing it efficiently. The results of this study have implications for the need for additional training and support for lecturers to improve their competence in E-evaluation implementation. This is important to ensure more effective integration in teaching and assessment methodologies and to maximize the benefits of technology in education.